(untitled) (Proceeding of the International Conference on Arts and Humanities, 2019)
Art lover Tagore was appreciative of cultural expression in dancing. For him, dance was the way of communication of souls. He put his soul efforts to make his students learn the aspects of all the Indian classical and folk dances and he appointed trained gurus in Shantiniketan. His hunger for cultural diversity in ashrama took him to the countries of global ends and he crossed over the boundaries of a ‘nation’ or a ‘religion’. He was open to every idea that was capable to express the soul emotion of his dance dramas. With every staging there were some changes in techniques and presentations that were the harvest of his dazzling creativity. He founded the base of a dance art that is flexible in structure and opens to adaptation and was used to present his dance dramas in and out of Shantiniketan. In sunset years of his life he finalize the staging and presentation of three natya-s; Chitrangda, Chandalika and Shyama. They were accepted as Rabindra Nritya Natya-s and the dance form is called Rabindra Nritya. The present paper is a study of Rabindra Nritya in his Nritya Natya-s, the viewpoint of Tagore behind it; it’s after developments and its cultural and philosophical value in present time.